2010
DOI: 10.1073/pnas.1005191107
|View full text |Cite
|
Sign up to set email alerts
|

miR-33 links SREBP-2 induction to repression of sterol transporters

Abstract: The sterol regulatory element binding protein 2 (SREBP-2) and the liver X receptor (LXR) control antagonistic transcriptional programs that stimulate cellular cholesterol uptake and synthesis, and cholesterol efflux, respectively. The clinical importance of SREBP-2 is revealed in patients with hypercholesterolemia treated with statins, which reduce low-density lipoprotein (LDL) cholesterol levels by increasing hepatic expression of SREBP-2 and its target, the LDL receptor. Here we show that miR-33 is encoded w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
501
1
13

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(545 citation statements)
references
References 40 publications
26
501
1
13
Order By: Relevance
“…SREBPs are helix-loophelix-leucine zipper transcription factors that play critical roles in cholesterol biosynthesis, while miR-33a and miR-33b, encoded within the introns of the srebp-2 and srebp-1 genes, respectively, are highly conserved and ubiquitously expressed miRNAs. 65 Recently, it was reported that miR-33a/b are co-regulated with their host genes under metabolic stimuli and they were identified as critical regulators of cholesterol homeostasis by three different groups. [65][66][67][68] In mouse and human, miR-33 inhibited the expression of the ABCA1, thereby inhibiting cholesterol trafficking.…”
Section: Lipid Homeostasismentioning
confidence: 99%
See 2 more Smart Citations
“…SREBPs are helix-loophelix-leucine zipper transcription factors that play critical roles in cholesterol biosynthesis, while miR-33a and miR-33b, encoded within the introns of the srebp-2 and srebp-1 genes, respectively, are highly conserved and ubiquitously expressed miRNAs. 65 Recently, it was reported that miR-33a/b are co-regulated with their host genes under metabolic stimuli and they were identified as critical regulators of cholesterol homeostasis by three different groups. [65][66][67][68] In mouse and human, miR-33 inhibited the expression of the ABCA1, thereby inhibiting cholesterol trafficking.…”
Section: Lipid Homeostasismentioning
confidence: 99%
“…65 Recently, it was reported that miR-33a/b are co-regulated with their host genes under metabolic stimuli and they were identified as critical regulators of cholesterol homeostasis by three different groups. [65][66][67][68] In mouse and human, miR-33 inhibited the expression of the ABCA1, thereby inhibiting cholesterol trafficking. Overexpression of miR-33 in macrophages and hepatocytes decreased cholesterol efflux to apoA1, while inhibition of miR-33 resulted in increased ABCA1 expression and cholesterol efflux.…”
Section: Lipid Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…2,46 The nutritional value of goat milk, especially fat composition and content ( 15,44 , can be further enhanced through dietary manipulation. 25,27,43 As a result, there have been several research studies on the molecular mechanisms regulating milk fat synthesis; however, they have been primarily focused on analyses of single gene function ( 20,54,61 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, miR-33a has been shown to target genes involved in cholesterol export, such as the ABC transporters ABCA1 and ABCG1 (46)(47)(48) and the endolysosomal transport protein Niemann-Pick C1 (Npc1). (48) In agreement with the regulation of ABCA1 by miR-33, modulation of miR-33a levels results in encompassing effects in cholesterol efflux in macrophages, thus suggesting that miR-33 may participate in the regulation of HDL levels in vivo.…”
Section: Mirnas In Glucose Homeostasismentioning
confidence: 99%